Meta-Analysis of the Effect of Local-Wisdom-Based Physics Learning on Students’ Learning Outcomes - Suarti Suarti; Suhardiman Suhardiman; Muh. Syihab Ikbal; Selviani Selviani; Risnawati Risnawati; Muh Yusuf Hidayat (Pendidikan Fisika UIN Alauddin Makassar, 2025)
This study is a Meta-Analysis study that aims to investigate the impact of Local Wisdom-Based Physics Learning on student learning outcomes at the SMA/MA level, to determine the impact of local wisdom-based learning on learning outcomes in physics learning based on class and based on subject matter. The type of research used is Meta Analysis, with the population used being all articles on the use of local wisdom-based physics learning and a research sample of 17 articles consisting of 13 national journals and 4 international journals using scientific articles that have been published through Google Scholar in 2013-2023 with predetermined criteria. The research instrument uses a coding sheet (data coding) and information on each research report in digital form, namely in Microsoft Excel, then analyzed using OpenMEE software. Based on the research conducted, it was obtained: (1) Local wisdom-based Physics Learning has a significant impact on student learning outcomes at the SMA/MA level with a Het value. P-Value <0.001, the impact of local wisdom-based physics learning on student learning outcomes is in the very large category with an average effect size of 2,558; (2) The impact of local wisdom-based physics learning on student learning outcomes for each class level at the SMA/MA level is significantly different, with an estimated effect size of class XI of 3,611, the highest compared to other levels, so that local wisdom-based physics learning is more effective if applied to class XI; (3) The impact of local wisdom-based physics learning on student learning outcomes based on subject matter is significantly different, with the highest estimated effect size for temperature material of 11,610 in the very large category compared to other materials. So that local wisdom-based physics learning is more effective when applied to temperature material. Local wisdom-based physics learning can be an option to be integrated into learning to improve student learning outcomes.